Multicentre Evaluation of the Naída CI Q70 Sound Processor: Feedback from Cochlear Implant Users and Professionals - Martin, Jeanette; Poncet-Wallet, Christine; Illg, Angelika; Perrin-Webb, Sarah; Henderson, Lise; Noël-Petroff, Nathalie; Auletta, Gennaro; Barezzani, Maria Grazia; Houri, Karim; Indian Research Group; Bagus, Heike; Hoppe, Ulrich; et al. (Audiology research, 2016)
The aim of this survey was to gather data from both implant recipients and professionals on the ease of use of the Naída CI Q70 (Naída CI) sound processor from Advanced Bionics and on the usefulness of the new functions and features available. A secondary objective was to investigate fitting practices with the new processor. A comprehensive user satisfaction survey was conducted in a total of 186 subjects from 24 centres. In parallel, 23 professional questionnaires were collected from 11 centres. Overall, there was high satisfaction with the Naída CI processor from adults, children, experienced and new CI users as well as from professionals. The Naída CI processor was shown as being easy to use by all ages of recipients and by professionals. The majority of experienced CI users rated the Naída CI processor as being similar or better than their previous processor in all areas surveyed. The Naída CI was recommended by the professionals for fitting in all populations. Features like UltraZoom, ZoomControl and DuoPhone would not be fitted to very young children in contrast to adults. Positive ratings were obtained for ease of use, comfort and usefulness of the new functions and features of the Naída CI sound processor. Seventy-seven percent of the experienced CI users rated the new processor as being better than their previous sound processor from a general point of view. The survey also showed that fitting practices were influenced by the age of the user.